From Continental Hyperextension to Seafloor Spreading: New Insights on the Porcupine Basin From Wide‐Angle Seismic Data. Issue 10 (23rd October 2018) - Chen, C.; Watremez, L.; Prada, M.; Minshull, T. A.; Edwards, R. A.; O'Reilly, B. M.; Reston, T. J.; Wagner, G.; Gaw, V.; Klaeschen, D.; Shannon, P. M.
Abstract: The deep structure and sedimentary record of rift basins provide an important insight into understanding the geological processes involved in lithospheric extension. We investigate the crustal structure and large‐scale sedimentary architecture of the southern Porcupine Basin, offshore Ireland along three wide‐angle seismic profiles, supplemented by 13 selected seismic reflection profiles. The seismic velocity and crustal geometry models obtained by joint refraction and reflection traveltime inversion clearly image the deep structure of the basin. Our results suggest the presence of three distinct crustal domains along the rifting axis: (a) continental crust becoming progressively hyperextended from north to south through the basin, (b) a transitional zone of uncertain nature, and (c) a 7‐ to 8‐km‐thick zone of oceanic crust. The latter is overlain by an 8‐km compacted Upper Paleozoic‐Mesozoic succession and 2 km of Cenozoic strata. Due to the lack of clear magnetic anomalies and in the absence of well control, the precise age of interpreted oceanic crust is unknown. However, we can determine an age range of Late Jurassic to Late Cretaceous from the regional context. We propose a northward propagating rifting process in the Porcupine Basin, resulting in variations in strain along the rift axis. Key Points: New analysis of wide‐angle seismic data from the southern Porcupine Basin Evidence for presence of oceanic crust in the southern Porcupine Basin. Jurassic rifting propagated from south to north, resulting in nonuniform strain when rifting stopped.